Emotional intelligence, spiritual intelligence, self-efficacy and health behaviors: implications for quality health - Omar Dev, Roxana Dev; Tengku Kamalden, Tengku Fadilah; Soh, Kim Geok; Abdullah, Maria Chong; Mohd Ayub, Ahmad Fauzi; Ismail, Ismi Arif (Human Resource Management Academic Research Society, 2018)
University students typically enter a dynamic transitional period of new independence from their parents that is characterized by many factors. These factors which involve social, financial, and environment elements, can be a burden to the students putting them at risk in negative health behaviours. Negative health behaviours among university students are a course of concern since they have a tendency to be carried into adulthood which can possibly cause the emergence of chronic disease at a younger age. Emotional intelligence, spiritual intelligence together with self-efficacy are seen to promote better health behaviour. Therefore, the purpose of the study was to investigate the relationship between emotional intelligence, spiritual intelligence and self-efficacy on health behaviours among university students in Universiti Putra Malaysia, Malaysia. A correlational study was conducted on 400 undergraduate university students who lived on campus and were chosen through stratified random sampling technique using closed ended questionnnaires (Schutte’s Self Report Emotional Intelligence, The Spiritual Self-Report Inventory, General Self Efficacy Scale and a modified version of Health Style Questionnaire). Pearson correlation and structural equation modelling were used to explore association between these aspects. Emotional intelligence, spiritual intelligence, self-efficacy and health behaviour were significantly correlated. Emotional intelligence and self-efficacy showed a partial mediation effect towards the relationship between spiritual intelligence and promoting health behaviour (p=0.0001). Thus, there was an association between spiritual intelligence with health behaviour, emotional intelligence with health behaviour, and self-efficacy with health behaviour. It is interpreted that spiritual intelligence can boost positive health behaviour and it is associated with emotional intelligence and self-efficacy relevantly gives benefit to health behaviour. Such data have important implications for both health practice and policy especially for higher education institutions.